Determining alternative clean energy sources for military bases - Holliday, Drew (My University, 2025)
This report is meant to investigate viable energy sources and to develop a process that can be implemented to determine the best sources to supply energy to military facilities throughout the United States. A case study of Minot Air Force Base, North Dakota utilizing the process developed in this report has been conducted to ensure an appropriate system can be selected from the energy sources listed in this report. The reasons that the military should identify alternate sources of energy to replace the common power grid and establish a process for determining the most viable option for facilities are national security, the recent introduction and improvements of energy production technology, and the opportunity to improve the public’s view on the military, though not discussed in much detail in this report. The alternate energy sources for this report were chosen to be wind, solar, nuclear power, enhanced geothermal, hydropower, hydrogen fuel cells, biomass, and tidal power. Following the goal of the Department of Energy to provide 100% clean energy, or net-zero greenhouse gas emissions, these sources were also identified as clean energy generation sources. Although there are other technologies being developed and may be in use, the energy sources selected are the most practical due to their increasing popularity and capability to be used microgrid systems, which are electrical systems with locally sourced energy that can be operated separate from the national power grid. These sources were also chosen because they are either in development or have been utilized in industry, leading to data that can be analyzed within this report. Theoretical sources that have not been assessed in some form were assumed to be unreliable until further data is collected. For this report, the source chosen with the developed process is meant to be the primary source of energy on a military base. Through the process of rating systems, other sources might also receive high ratings, indicating they might be a slightly less preferred but still viable option for energy production. To ensure that military facilities always have electrical power, the national power grid will be utilized as backup power for when the selected system is not operational. For the process of determining an alternate source to power a military base, a set of criteria had to be chosen in which to evaluate and select the best source. The criteria that this report utilizes are location availability, security, reliability, capability, efficiency, constructability, and the maintenance of the system. Though this list is not all-encompassing of all the decisions included in selecting energy sources, this list of criteria was chosen because together they can indicate the overall expectation of how a system might perform. Cost will not be used within this report as a rating factor as the best system may or may not be the most expensive. By not rating systems based on cost, the best system can be selected to ensure a more stable infrastructure that the military can rely on. The location availability and capability categories show whether a system can sustain the base’s electrical demand in the given location and will determine the land usage needed to meet the electrical demand. The security, reliability, and maintenance categories are used to determine whether the energy system is an acceptable option for the military that supports its mission to protect the US from enemies, both foreign and domestic, and the need to always remain functional throughout the year. The efficiency and the constructability categories were chosen to determine whether a system fits the military’s requirements for utilizing the best system available. The efficiency of the system can aid in determining the resource utilization of the system and constructability can include whether a system can be constructed in time to secure infrastructure stability while reducing the need for frequent replacements of a system that could lead to threats in national security. This report suggests that a rating scale from one to five can indicate how energy sources compare to each other while allowing for an energy source to be identified as the best energy source for a base to adopt.
Keywords: Energy; Military